Une vision européenne de l’île - Nickel, Beatrice (Romanica Silesiana)
In his Discourse on the Origin and Basis of Inequality Among Men (Discours sur l’origine et les fondements de l’inégalité parmi les hommes, 1755) Jean‑Jacques Rousseau argued that man, in a state of nature, was inherently good, but became depraved the moment he decided to live in societies. In 18th century European literature, Rousseau’s idea assumed shape in the description of the original inhabitants of Tahiti. For the first time, Louis Antoine de Bougainville described them as the embodiment of Rousseau’s natural man. At this very moment, Tahiti became, in the European imagination, the epitome of paradise on earth. Beside the account of Bougainville’s journey, the following paper is focussed on literary texts of James Cook, Georg Forster and Denis Diderot. Key words: Tahiti, the Enlightenment, bon sauvage, utopian thought